Pré-tratamento das vitaminas B1, B2, B3, B6 , BB12 e C para a determinação de cádmio e chumbo por voltametria de redissolução anódica - Schirmer, Sabrina (2005)
The present work approaches pretreatment steps for the determination of cadmium and lead, as contaminants, in water soluble vitamins of samples, vitamins B1, BB2, B3, B6, B12, and C, for anodic stripping voltammetry (ASV). The vitamins are necessary in the human diet, because they cannot synthesize these compounds. The B1, B2, B3, B6, B12 and C vitamins possess an important role in the human metabolism and its deficencies can cause several diseases. The cadmium and lead are metals high toxics, having deleterious effects on several human organs. These metals in vitamins samples can hinder essencial action of these and depending on the levels of this contamination to offer toxicological risks to the human health. The direct determination of cadmium and lead by ASV in the presence of these vitamins were not possible, possibly due to interactions of these vitamins with the metals or with the mercury electrode. For this reason, it was studied pretreatment alternatives for the vitamins samples with the purpose of determining cadmium and lead by ASV. The vitamins B1, B2, B3, B6, B12 and C were analyzed individually after the pretreatments by wet digestion, microwave digestion and ultraviolet digestion. The best results of the voltammetric determination of cadmium and lead were obtained with the pretreatment by UV digestion, using sample with dilution 1:10, 20 μL of nitric acid, 50 μL of hydrogen peroxide before beginning the irradiation and 50 μL after 60 minutes of irradiation, temperature of 90º C ± 3 for 6 hours. The obtained recovery results of the voltammetric determination, using the ultraviolet digestion, for the samples B1, B2, B3, B6, B12 and C vitamin was of 90,15; 91,7; 101,4; 95,35; 94,8 and 94,8% for cadmium and of 113; 102,2; 107,5; 106,5; 90,35 and 91,4% for lead, respectively.